MODELLING OF THE PROCESS OF TEACHING READING ENGLISH LANGUAGE PERIODICALS - Тетяна Глушко (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2014)
The article reveals a scientifically substantiated process of teaching reading English language periodicals in all its components, which are consistently developed, and form of interconnection of the structural elements in the process of teaching reading. This process is presented as a few interconnected and interdetermined models: 1) the models of the process of acquiring standard and expressive lexical knowledge; 2) the models of the process of formation of skills to use such vocabulary; 3) the models of the development of skills to read texts of the different linguistic levels.